2016
DOI: 10.15408/es.v7i2.1815
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pembelajaran Process Oriented Guided Inquiry Learning Terhadap Keterampilan Proses Sains Dan Kemampuan Kognitif Siswa Pada Mata Pelajaran Fisika

Abstract: The study in this paper is based on the results of literature study, journals and research findings on proces oriented guided inquiry learning (POGIL) that focus on the implementation of POGIL and the influence of POGIL in building science process skills and student cognitive abilities. From the results of the study, it was found that POGIL could improve science process skills, thinking skills, train problem solving skills, enhance the mastery of subject matters, and improve student cognitive abilities. POGIL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 1 publication
1
8
0
3
Order By: Relevance
“…From these results, it can be concluded that the POGIL model has an effect on students' process skills. This is in line with previous research which states that POGIL can improve science process skills for students (Alatas & Fachrunisa, 2018;Idul & B. Caro, 2022;Zamista & Kaniawati, 2015). The difference in process skills between the experimental class and the control class can be caused because, in the inquiry model learning, learning activities are not only in the form of knowledge transfer from teachers and students.…”
Section: Influence Of the Pogil Model On Students' Science Literacy A...supporting
confidence: 90%
“…From these results, it can be concluded that the POGIL model has an effect on students' process skills. This is in line with previous research which states that POGIL can improve science process skills for students (Alatas & Fachrunisa, 2018;Idul & B. Caro, 2022;Zamista & Kaniawati, 2015). The difference in process skills between the experimental class and the control class can be caused because, in the inquiry model learning, learning activities are not only in the form of knowledge transfer from teachers and students.…”
Section: Influence Of the Pogil Model On Students' Science Literacy A...supporting
confidence: 90%
“…The research found that guided inquiry model can be used to improve the physics learning outcomes in students on chapter static fluid. Other research also found that guided inquiry learning model was able to enhance student' conceptual understanding and students' cognitive abilities (Zamista & Kaniawati, 2015).…”
Section: Communicatingmentioning
confidence: 98%
“…Sejumlah penelitian diatas mendukung kajian literatur bahwa POGIL dapat meningkatkan keterampilan proses, kemampuan berpikir, keterampilan menyelesaikan masalah (problem solving), dan meningkatkan kemampuan kognitif siswa (Zamista & Kaniawati, 2016). Pembelajaran POGIL cocok digunakan untuk rumpun eksakta seperti fisika dan kimia sebab rumpun tersebut merupakan bagian dari proses sains dan terdapat metode ilmiah.…”
Section: Pembahasanunclassified